• Welcome to our site! Electro Tech is an online community (with over 170,000 members) who enjoy talking about and building electronic circuits, projects and gadgets. To participate you need to register. Registration is free. Click here to register now.

a + jb

Not open for further replies.


Well-Known Member
Most Helpful Member
You would solve it like any other equation...isolate z. Then you manipulate the expression to get it into the form of a+jb. One trick is that since j*j = -1, you can multiply expressions like (x+jy) by it's conjugate divided by it's conjugateTHis means you would multiply the expression by (x-jy) / (x-jy) = 1. Since it's equal to one, you aren't changing the expression. YOu are just changing the way it looks.

(x+jy)*(x-jy)/(x-jy) = (x^2+y^2)/(x-jy).

What this lets you do is move the complex j expression between the numerator and denominator. ANd if you do it right, it probably divides itself out, or puts the j in a place where you want it.
Last edited:
First thing I would do is convert that mess on the right side of the '=' sign to Steinmetz form.

If: C= a + jb (Cartesian) then

R= sqrt(a^2 + b^2)

Theta= arctan(b/a)

C= R /_ Theta (Steinmetz)

That makes exponentiation and division relatively straight forward.

C^x= R^x /_ (Theta * x)


A= Ra /_ Thetaa

B= Rb /_ Thetab

A / B= (Ra / Rb) /_ (Thetaa - Thetab)


A X B= (Ra X Rb) /_ (Thetaa + Thetab)

If you want it in Cartesian form:

a= Rcos(Theta)

b= jRsin(Theta)
Last edited:
Not open for further replies.

Latest threads

EE World Online Articles